MODALITY IN TEACHER-TO-TEACHER TALK OF ONLINE LEARNING: TENOR IN LANGUAGE USE - Laoli, Citra Indah Maharani (Journal of Language, Literature and Teaching, 2025)
AbstractThe objective of this study was to identify the reasons behind the realization of modality in teacher-to-teacher talk of online learning. The data of this study consisted of sentences that expressed modality, uttered by five primary school teachers as they discussed online learning. In addition, the teachers’ responses during interviews were also used to provide deeper insights into the reasons for their use of modality. The data were collected by using three main instruments, namely: observation sheet, interview sheet, and voice recorder. The data analysis followed the three stages of qualitative data analysis, namely: data condensation, data display, and drawing and verifying conclusions. The findings revealed that the use of modality in teacher-to-teacher talk of online learning was affected primarily by tenor. This includes the roles the teachers played during the interaction, which were shaped by elements such as power, contact, affect, and formality. Furthermore, modality was also realized due to the values that teachers attached to online learning. Most of the teachers expressed negative attitudes and preferences, indicating dissatisfaction or discomfort with the practice. Therefore, it is important for the government and policymakers to take teachers’ perceptions into account when designing and implementing educational policies, particularly those involving online learning in Indonesia.Keywords: modality, teacher-to-teacher talk, online learning, tenor.